EFEKTIVITAS PENYULUHAN KESEHATAN DALAM MENINGKATKAN PENGETAHUAN KELUARGA TENTANG OBESITAS PADA ANAK SEKOLAH - Eko Riyanti, Eka Puji Lestari (AKPER Pemkab Purworejo, 2020)
According to the Basic Health Research Survey Data (RISKESDAS) in 2018, the incident of obesity has increased significantly in children, which was 26,6 % to 31,0 %. In the field observation made at An’s house N and An. A with interview and action methods to 2 families who have children aged 6-12 years, it was concluded that two family members did not know the problem of obesity and how to overcome obesity, this happened because of the lack of knowledge from both parents, heredity, and others. Objective : To determine the level of parental knowledge about obesity in An. N and An. A in the village of Bapang Sari and Dadirejo in 2019. Method : This research uses descriptive method with cross sectional design. In this study the authors took 2 families at the developmental stage of school children aged 6-12 years in different villages with the same health problem namely obesity. Data collection was carried out bydistributing checklist about obesity to family. The nutritional status of children is determined by measuring the child’s height and weight. Result : After being given health education about the problem of obesity in both families the level of knowledge increased from 20% to 80% and 40% to 70%. Conclusion: Health education is effective in increasing family knowledge about obesity in school children.